KEEFEKTIFAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA DIORAMA TERHADAP HASIL BELAJAR IPA KELAS V SDN 02 PESUCEN - Indah Wijayanti; Rais, Rahmat; Azizah, Mira (STKIP Subang, 2020)
The purpose of this study was to determine the effectiveness of the Problem Based Learning model with diorama media on the science learning outcomes of class V SDN 02 Pesucen Pemalang. This type of research is a quantitative experiment. This research is a Pre-Experimental Design with the form of experimental design used is the One-Group Pretest-Posttest Design. The research subjects were grade V students of SDN 02 Pesucen Pemalang in the academic year 2020/2021. The research sample was taken by using nonprobability sampling technique. Data collection techniques using tests, documentation, interviews, questionnaires and questionnaires. The results of the research carried out in class V SDN 02 Pesucen showed that there was a difference in the average acquisition of posttest and pretest scores, namely the pretest results of 58.645 while the posttest results were 82.968, this shows that the Problem Based Learning model with diorama media is effective for improving science learning outcomes. students. Based on the analysis of the hypothesis using the t-test, obtained tcount> ttable, namely 10.550> 2.042, so Ho is rejected and Ha is accepted. So the conclusion is that the problem based learning model assisted by diorama media is effective on the science learning outcomes of fifth grade students of SD Negeri 02 Pesucen.